Insight Into Novel Anti-tuberculosis Vaccines by Using Immunoinformatics Approaches - Khan, Zafran; Ualiyeva, Daniya; Amissah, Obed Boadi; Sapkota, Sanjeep; Hameed, H. M. Adnan; Zhang, Tianyu (Frontiers in Microbiology, 2022)
Tuberculosis (TB) is an infectious disease that has severely affected vulnerable populations since time immemorial. The causal agent of TB is the Mycobacterium tuberculosis (Mtb) which can attack many parts of the body, mainly the lungs. Mycobacterium bovis Bacillus Calmette-Guerin (BCG) is the only approved vaccine for TB, but its efficiency to combat pulmonary TB is limited. Multidrug-resistant (MDR) TB and extensive drug-resistant (XDR) TB requires the evolution of more potent vaccines. Therefore, this research aims to generate a universal TB subunit vaccine using advanced immunoinformatics techniques. In generating a novel multiepitope subunit vaccine, we selected the conserved and experimentally confirmed antigens Rv0058, Rv0101, and Rv3343. After a rigorous evaluation, the top candidates from predicted Helper T lymphocytes (HTL), Cytotoxic T lymphocytes, and B-cell epitopes were considered potential vaccine candidates. Immunogenicity was enhanced by adding an adjuvant to the ultimate construct of the vaccine. B-cell epitopes predictions guaranteed the eventual induction of a humoral response. Thereafter, dynamics simulations and molecular docking validated the vaccine-receptor complex’s stability and high affinity for the immune receptor TLR-3. Also, immune simulations revealed significantly elevated levels of immunoglobulins such as IgM, cytokines such as Interleukin-2, and helper and cytotoxic T-cell populations. These results agreed with the actual inflammatory response and showed rapid antigen clearance after manifold exposure. Finally, the E. coli K12 strain was confirmed via in-silico cloning for quality expression. Nevertheless, experiments should be done to validate the safety of the proposed vaccine and its inherent ability to prevent TB infection.